The Trends of Clinical Symptoms and Hematological Problem’s of Patients with Dengue Fever in Tertiary Care Hospital in Year 2011 - TALAT NAHEED, MOHAMMED NAEEM, RASHID IQBAL, KHALID MAHMUD KHAN (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the trends of clinical symptoms and hematological profile of dengue fever patients admitted in Tertiary Care Hospital. Study design: Retrospective Observational Study Setting: The study was done in department of Medicine of Sir Ganga Ram Hospital. Timing: from 1-09- 2011 to 30-11-2011 Methods: This paper describes the trend of clinical manifestation and hematological findings of 453 hospitalized patients in Sir Ganga Ram hospital Lahore. Patients were divided into two groups on the basis of platelet level and liver function test level. The objective of categorization was to find out the trend of hematological characteristics of severe disease group from that of mild disease. This open label Retrospective observational study was carried out in department of medicine Sir Ganga Ram Hospital Lahore from 1st September 2011 to 30 November 2011. Analysis of frequency of symptoms and hematological profile was done in these patients to identify the labortary outcomes of these patients. Results: Among 453 patients admitted in tertiary care hospital with fever and thrombocytopenia, 321 patients had dengue fever and 132 had DHF. All these were differentiated on the bases of Ultrasound of abdomen and Chest x-ray to look for signs of plasma leak. Among dengue fever patient’s 283 patients had platelet less than 50000. Among DHF patients, 129 patients had platelets count less than 50000. Among 453 patients, 63 patients had IGM positive, 71 had IgM and IgG positive and 319 had IgG positive. It was also found that among 453 patients, 110 patients have liver function test disturbance 30 patients were dengue fever and 79 were dengue hemorrhagic fever among these 6 patients were having severe liver dysfunction ( LFTS greater than Five times of normal). Conclusion: It was found that severe thrombocytopenia was seen (platelet less than 50000) in dengue fever admitted in tertiary care hospital and this was unusual finding in dengue fever patients admitted in tertiary care hospital during admission. It was also proven severe liver dysfunction (LFTS greater than of five times of normal) was found in only dengue haemerrhegic fever.